Supply chain cooperation and company performance - Ratajczak-Mrozek, Milena; Małys, Łukasz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The article presents analysis of the performance of companies characterized by varying approaches to formal and informal cooperation within the supply chain. The authors have identified and compared the performance of three groups of companies: cooperating with external entities only formally, cooperating only informally and cooperating both formally and informally. The first main contribution of the paper is the inclusion of informal cooperation into companies' cooperation analysis. The second is relating cooperation to a company's performance. The conclusions may be of practical importance. By presenting the positive relations between cooperation and performance, companies may determine the sources which may increase their advantage over competitors
Argumenta Oeconomica, 2012, Nr 2 (29), s. 89-108
Keywords: cooperation; informal cooperation; supply chain management; company performance; competitiveness; współpraca; zarządzanie łańcuchem dostaw; konkurencyjność przedsiębiorstwa